Dynamics of Biological Systems. - Small, Michael (Chapman and Hall/CRC mathematical & computational biology series., 2011)
Biological Systems and Dynamics In the Beginning The Hemodynamic System Cheyne-Stokes Respiration Population Dynamics of a Single Species Fibonacci, Malthus and Nicholsons Blowflies Fixed Points and Stability of a One-Dimensional First Order Difference Equation The Cobweb Diagram An Example: Hormone Secretion Higher Dimensional Maps Period Doubling Bifurcation in Infant Respiration Observability of Dynamic Variables Bioelectric Phenomena Measurement ECG, EEG, EMG, EOG and All That Measuring MovementMeasuring Temperature Measuring Oxygen Concentration Biomedical Imaging The Importance of Measur.